Rethinking how volatiles are released from plant cells. (September 2015) - Widhalm, Joshua R.; Jaini, Rohit; Morgan, John A.; Dudareva, Natalia
Highlights Modeling shows mM VOC levels must be present in membranes for emission to occur via passive diffusion. We suggest that biological mechanisms contribute to VOC emission and lower concentrations in membranes. The cuticle provides the highest resistance to VOC emission.